SOUTH CAUCASIAN COUNTRIES: SOCIOECONOMIC DEVELOPMENT AND DEMOGRAPHIC POTENTIAL IN THE NEW GEOPOLITICAL CONDITIONS - PISMENNAYA, Elena; RYAZANTSEV, Sergey; PICHKOV, Oleg; LUKYANETS, Artyom (CENTRAL ASIA AND THE CAUCASUS, 2017)
The article considers the specific features of socioeconomic and demographic development in the three South Caucasian countries in the new geopolitical conditions. It identifies the demographic trends in Armenia, Azerbaijan, and Georgia, shows the specific factors behind these trends, and describes fertility, mortality, and migration processes in the three countries. In particular, it shows the specific patterns of emigration from the South Caucasian countries, including to the Russian Federation, as well as the new geographical destinations for migrants from the region. The authors note that the diasporas formed as a result of emigration have contributed to socioeconomic stability in the region. Thanks to material support from the diasporas, their home countries have managed to stabilize the socioeconomic situation, maintain the income level of a significant part of the population, and avoid mass unemployment and poverty. As the socioeconomic situation has stabilized, the development of the South Caucasian countries has become more uneven. The best situation is in Azerbaijan, which is relatively rich in fossil fuel, while the situation in Armenia and Georgia is much worse. Demographic processes in the Southern Caucasus also differ from country to country: the most favorable demographic situation is in Azerbaijan, and the least favorable in Georgia. Azerbaijan also has the most balanced age and sex structure of the population. Armenia and Georgia, despite rising birth rates, still have negative population growth due to migration outflows.